Cu2O quantum dots modified by RGO nanosheets for ultrasensitive and selective NO2 gas detection. Issue 11 (1st August 2017) - Zhou, Yong; Liu, Guoqing; Zhu, Xiangyi; Guo, Yongcai
Abstract: Real-time monitoring of trace NO2 emission has been an emerging challenge in environment and health sectors lately. Aiming to overcome this challenge, NO2 gas sensors based on cuprous oxide quantum dots (Cu2 O QDs) anchored onto reduced graphene oxide (RGO) nanosheets serving as a sensitive layer were prepared in this report. Apart from a series of purposive measurements, various characterization techniques such as XRD, Raman, XPS and TEM were employed as well to assist the exploration of sensors performance to NO2 gas. The experimental results revealed a 580% response enhancement for prepared RGO/Cu2 O sensors compared with pure RGO counterparts, as well as an excellent selectivity. In a specific experiment, the sensing response attained 4.8% and 29.3% toward 20 ppb and 100 ppb NO2 respectively at 60 °C, which was larger than most Cu2 O based resistive gas sensors. Moreover, further subtle modulation of this RGO/Cu2 O nanocomposites led to a preferable room-temperature response of 37.8% toward 100 ppb NO2, which also offered a favorable stability of 98.1% response retention after four exposures within ten days. The obtained results imply that the prepared RGO/Cu2 O QDs sensors possess a competitive capability of trace NO2 detection.